Development of a flow‐sensitive macroinvertebrate index for Australian rivers. (2nd March 2022) - Chessman, Bruce C.; Metzeling, Leon; Robinson, David P.
Abstract: Hydrologically sensitive macroinvertebrate indices have been developed in Europe, the Americas and New Zealand to serve many purposes such as monitoring ecological responses to drought, flow regulation, water extraction and the provision of environmental flows. We created an Australian Macroinvertebrate Flow Index (AMFI) based on relative current‐velocity preferences of numerous Australian invertebrate families and genera, derived from a large dataset composited from past biomonitoring programs. We tested the new index with datasets independent from those used for its derivation, showing that it correlated strongly with current velocity and responded mostly as expected to discharge fluctuations downstream of a large dam. A genus‐level version was more responsive than a family‐level version, but the sensitivity of the family‐level version was improved by the incorporation of weighting based on taxon abundance. We suggest possible uses of the new index and recommend further development and testing, particularly in relation to intermittent streams and environmental flows.